2016
DOI: 10.1007/s00213-016-4492-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration and behavioral economics of second-generation synthetic cathinones in male rats

Abstract: Rationale Synthetic cathinones have become increasingly available as drugs of abuse. Distribution of these drugs is made possible by altering the chemical structures of prohibited cathinones and marketing them under misleading labels. Very little is known about the relative reinforcing effectiveness of new synthetic cathinones relative to known drugs of abuse. Objective We examined self-administration of three second-generation synthetic cathinones: alpha-pyrrolidinopentiophenone (alpha-PVP), 4-methyl-N-ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…The present study characterized the reinforcing effects of four second-generation cathinones, and found that responding for each of these cathinones was rapidly acquired and not different from previous reports for the first-generation cathinone, MDPV (Gannon et al 2017b). Although self-administration of α-PVP (DEA Schedule I) has previously been described (Aarde et al, 2015a; Gannon et al, 2017c; Huskinson et al, 2017), these studies provide new and important information about the reinforcing effects of MDPBP, MDPPP, and α-PPP, and suggest that they each possess a high potential for abuse. In addition, all four of these synthetic cathinones established high levels of drug intake and/or compulsive-like patterns of responding during post-infusion timeouts in a subset of rats.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The present study characterized the reinforcing effects of four second-generation cathinones, and found that responding for each of these cathinones was rapidly acquired and not different from previous reports for the first-generation cathinone, MDPV (Gannon et al 2017b). Although self-administration of α-PVP (DEA Schedule I) has previously been described (Aarde et al, 2015a; Gannon et al, 2017c; Huskinson et al, 2017), these studies provide new and important information about the reinforcing effects of MDPBP, MDPPP, and α-PPP, and suggest that they each possess a high potential for abuse. In addition, all four of these synthetic cathinones established high levels of drug intake and/or compulsive-like patterns of responding during post-infusion timeouts in a subset of rats.…”
Section: Discussionmentioning
confidence: 88%
“…In rodents, MDPV, α-PVP, α-PPP, and MDPBP have been shown to increase locomotor activity and produce cocaine-, methamphetamine-, and MDMA-like discriminative stimulus effects (e.g., Collins et al, 2016; Fantegrossi et al, 2013; Gannon et al, 2016; Gatch et al, 2013, 2015, 2017; Naylor et al, 2015). MDPV and α-PVP have also been shown to facilitate intracranial self-stimulation and maintain self-administration in rats, suggesting that they function as reinforcers (e.g., Aarde et al, 2015a; 2015b; Gannon et al, 2017a; 2017b; 2017c; Huskinson et al, 2017; Watterson et al, 2014a, 2014b). Additionally, it has been shown that a subset of rats trained to self-administer MDPV (but not cocaine) develop a persistent “high-responder” phenotype, characterized by high levels of drug intake and increased responding during post-infusion timeouts (Gannon et al, 2017b), an effect that may be related to the selective actions of MDPV at DAT relative to SERT (SERT/DAT ~100-800) (Baumann et al, 2013; Eshleman et al, 2013; Simmler et al, 2013).…”
Section: Introduction1mentioning
confidence: 99%
“…Intravenous catheters were implanted and maintained as described previously (Huskinson et al 2017). Rats were allowed to recover for 5–7 days following surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-five Sprague-Dawley rats (18 males, 17 females) were acquired at 10 weeks of age (Envigo Laboratories, Frederick, MD, USA) and surgically implanted with custom-made jugular catheters and vascular access ports (Instech, Plymouth Meeting, PA, USA) as described previously [27]. Rats were singly housed in a temperature-and humidity-controlled vivarium that was maintained on a 12-h light/dark cycle (lights off at 6:00 p.m.).…”
Section: Subjectsmentioning
confidence: 99%